Comparison of Bilateral Cerebro-Renal Tissue Oxygenations in Healthy Children - UYAR, EMEL; ÖZTÜRK, MAKBULE NİLÜFER (SPRINGER INDIA, 2020)
Objective To investigate right and left cerebral tissue (ctSO(2)) and renal tissue oxygenations (rtSO(2)) in otherwise healthy children. Methods In this observational cross-sectional study, one hundred children seen as outpatients for well child care or common non-critical complaints, were included. Bilateral ctSO(2) and rtSO(2) were recorded simultaneously with INVOS (TM) 5100 device. Results The median age was 6.7 y (IQR 3-10.4) and median weight was 21 kg (IQR 13-33). Right and left sided ctSO(2) and rtSO(2) values were 78.7% +/- 6.0% and 79.1% +/- 5.7%; 81.5% +/- 9.4% and 81.4% +/- 9.5% respectively. There were no differences in right and left cerebral and renal near infrared spectroscopy (NIRS) values, and no age centered lateralization effect. Renal measurements were higher than cerebral counterparts in 63% of the children. Interaction between age and regional oxygenation was significant. For both sides, renal oxygenation was higher than that of cerebrum in older children, whereas the opposite held true with younger age. Conclusions There are no right and left side differences in ctSO(2) and rtSO(2) values in otherwise healthy children. On the other hand, there seem to be differences between cerebral and renal regions with a significant age effect. Acknowledging its limitations, this study sheds light on laterality and cranial and renal NIRS measurements in otherwise healthy children, and may contribute to the interpretation of NIRS data in critically ill patients.
Keywords: Near infrared spectroscopy; Tissue oxygen saturation; Regional; Children; Bilateral measurement; NEAR-INFRARED SPECTROSCOPY; REFERENCE RANGES; SATURATION; TRANSITION; EXTRACTION; OXIMETRY; INFANTS; DEVICES; INDEX